Muscle and fat quality of Chinese soft-shelled turtle - ZHAN Xiu-an; XU Zi-rong; QIAN Li-chun (浙江大学学报. 农业与生命科学版)
Experiments were carried out to study on the content of moisture, crude protein and lipid of muscle and fatty block, and of mineral element and amino acid of muscle, and on the fatty acid composition of muscle and fatty block in Chinese soft-shelled turtles (Trionyx sinensis). Results showed that protein and lipid content in muscle were 18.21% and 1.23% respectively, and lipid content of fatty block was 86.72%. It was found that there were rich trace mineral elements of important physiological functions in muscle, in which iron and chromium content were 380.13 mg/kg and 1.08 mg/kg. The essential amino acids and delicious amino acids in muscle accounted for 46.94% and 45.45% of total amino acids respectively, in which glutamic acid and aspartic acid content were highest, reaching about 11.90% and 7.94%. The fatty acids of muscle and fatty block contained 30.18% and 24.96% of high unsaturated fatty acids, among which EPA (Eicosapentaenoil acid) and DHA (Docosaheraenoic acid) content were 9.93% and 9.12%. On the basis of above results, the nutrient value and health-keeping value of turtle were confirmed.